Implementasi Keterampilan Mengelola Kelas Oleh Guru PPKn di SMK Negeri 1 Motoling Timur - Sara Mika Timporok; Julien Biringan; Wua Telly Delly (CV. Kurnia Grup, 2026)
This study aims to describe the implementation of classroom management skills by Pancasila and Citizenship Education (PPKn) teachers at SMK Negeri 1 Motoling Timur. This study uses a normative descriptive method with a qualitative approach. The subjects in this study are PPKn teachers and students at SMK Negeri 1 Motoling Timur. Data collection techniques are carried out through observation and interviews. The validity of the data is tested using source triangulation to obtain valid and reliable data.The results of the study show that the implementation of classroom management skills by PPKn teachers has been carried out well through learning planning, varied implementation, and learning evaluation. Teachers use various strategies such as lecture methods, discussions, questions and answers, and the use of learning media to create an active and conducive classroom atmosphere. In addition, teachers also apply a discipline approach through class rules, examples, habituation, and the provision of rewards and punishments in shaping student discipline behavior. Students respond positively to the way the teacher manages the classroom and demonstrate discipline and active involvement in learning. Thus, it can be concluded that the skills of managing classes by PPKn teachers at SMK Negeri 1 Motoling Timur have been implemented effectively in creating an orderly, conducive, and supportive learning process for students.